Estrategias didácticas innovadoras y Trastorno por Déficit de Atención e Hiperactividad en niños de cuarto grado, Unidad Educativa Pio Jaramillo Alvarado, periodo 2024-2025 - Jara González, Paola Stefanía (2025)
This integrative curricular project allowed us to understand the reality, gain a better understanding of the specific needs, and learn which tools can be used with children with attention deficit hyperactivity disorder (ADHD) in the fourth grade at Unidad Educativa Pio Jaramillo Alvarado during the 2024-2025 period, developing mechanisms to enable children with ADHD to achieve their full potential, the research also made it possible to identify their main characteristics, the obstacles they face in the educational environment, the innovative strategies used by professionals to provide pedagogical support for overcoming the main challenges, and the benefits of using the right tools. This, in turn, aims to improve the quality of education and the well-being of students in the classroom. By understanding these innovative practices, educators can enhance and enrich their teaching experience, while also personalizing academic tasks to meet students' diverse needs, abilities, and interests. Through the application of tools such as interviews and observation sheets, data was collected that led to the development of a methodological guide called: “Guide to Didactic Strategies for Children with Attention Deficit Hyperactivity Disorder (ADHD)”, with the main objective of providing teaching strategies to work on attention, self-control, and emotions within the classroom. It also aims to offer techniques for addressing the primary challenges faced by students. Additionally, the guide provides resources to develop attention, both short- and long-term memory, participation, interpersonal skills, motivation in the teaching-learning process, and improvements in behaviour and self-esteem. It contributes to the creation of an educational system that fosters inclusion, with a collaborative and effective environment